Rare Case of Lumbosacral Conjoint Root Diagnosed as Sequestered Disc by MRI: A Case Report - Akram Awadallah (Journal of Spine Practice)
Introduction: Conjoint nerve root is embryological nerve root abnormality mainly affecting lumbosacral region. The atypical roots present primarily as a bifid, conjoined structure originating from a wide area of the dura. The conjoint roots are highly liable to trauma due to their size and attachment to surrounding structures. The effects of compression and entrapment are augmented in the case of having stenosis of the lateral recesses where developmental changes and disc herniations deplete the available reserve space. Conjoined nerve roots are a relatively uncommon finding but are frequently left undiagnosed on preoperative imaging studies. Misinterpretation as sequestered disc can lead to devastating results especially during limited spine approach.